Water Extract of Rhizoma Drynaria Selectively Exerts Estrogenic Activities in Ovariectomized Rats and Estrogen Receptor-Positive Cells - Zhou, Liping; Wong, Ka-Ying; Poon, Christina Chui-Wa; Yu, Wenxuan; Xiao, Huihui; Chan, Chi-On; Mok, Daniel Kam-Wah; Wong, Man-Sau (Frontiers in Endocrinology, 2022)
Our previous study demonstrated that the bone protective actions of herbal medicine Rhizoma Drynariae (Gusuibu, RD) were mainly mediated by flavonoid phytoestrogens via estrogen receptors, raising concerns about the safety of using RD as it may induce estrogen-like risk-benefit profile and interact with other ER ligands, like Selective Estrogen Receptor Modulators (SERMs) when co-administered. The present study evaluated the estrogenic activities of RD and its potential interaction with tamoxifen, a SERM, in estrogen sensitive tissues by using mature ovariectomized (OVX) rats and ER-positive cells. Similar to but weaker than tamoxifen, RD at its clinical dose dramatically ameliorated OVX-induced changes in bone and dopamine metabolism-related markers in OVX rats. However, tamoxifen, but not RD, induced uterotrophic effects. Stimulation in mammary gland was observed OVX rats treated with RD, which was different from the inhibitory actions of tamoxifen. The Two-way ANOVA results indicated the interactions between RD and tamoxifen in bone, brain and uterus of OVX rats while RD did not alter their responses to tamoxifen. Our results demonstrate that RD selectively exerts estrogenic actions in different manner from tamoxifen. Moreover, RD interacted with tamoxifen without altering its effects in OVX rats.